Progress of Gender and Development Mainstreaming in Agricultural Cooperatives in Bulacan, Philippines - Esguerra, Imee D.; Alonzo, Ronald Reagan T.; Villena, Billy Joe V.; Buenaventura, Rodrigo G.; McNatt, Aisanne Marie S. (Connexion: Journal of Humanities and Social Sciences, 2023)
The main goal of cooperatives to empower economically disadvantaged members of society should be reflected in how they value women members who are often victims of gender bias and stereotyping. Hence, women’s participation and gender equality in operational policies of agricultural cooperatives in Bulacan, Philippines were assessed to determine the progress of gender and development mainstreaming in this institution. A descriptive correlational research design using survey questionnaires and follow-up interviews was employed for two groups of respondents composed of 20 cooperative officers and 289 women members. Frequency count, percentage distribution, weighted mean, Pearson’s R Correlation, and Analysis of Variance (ANOVA) were the statistical tools used. Results showed that the operational policies of respondent cooperatives were not yet gender-responsive and the extent of women’s participation is very low. Women mostly occupied management staff positions. Notably, women were least active in the gender and development (GAD) committee which is only partially functional. Lots of work and places to go and too many household chores were the top two problems encountered by women. Educational attainment and source of income were computed as significant factors with the extent of women’s participation regardless of the roles they performed. A lot still remains to be done to mainstream gender and development in agricultural cooperatives.